Moderasi Islam di Era Digital: Media Sosial, Narasi Onile, dan Tantangan Ekstrimisme - Muhamad Hoiri; M. Muizzuddin (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
This study examines the dynamics of Islamic moderation in the digital era by focusing on the role of social media, online religious narratives, and the challenges of extremism. The rapid growth of digital technology has transformed the way Islamic discourses are produced, disseminated, and consumed, with social media emerging as a central arena for ideological contestation between moderate and extremist narratives. Employing a qualitative approach through literature review and digital content analysis, this research explores how the values of Islamic moderation are represented, negotiated, and promoted in online spaces. The findings indicate that social media holds significant potential for strengthening Islamic moderation through inclusive da‘wah, inter-ideological dialogue, and digital religious literacy. Nevertheless, digital platforms are also vulnerable to being exploited by extremist groups to spread radical and intolerant ideologies. Therefore, reinforcing moderate Islamic narratives, enhancing digital literacy, and fostering collaboration among religious leaders, educators, and the wider community are crucial strategies for addressing the challenges of extremism in the digital age.